Evaluation of anaerobic capacity in soccer players using a maximal shuttle run test - de Almeida, Alexandre Gomes; Pereira, Gleber [UNESP]; Campeiz, José Mário; Maria, Thiago Santi (My University, 2009)
The aim of this study was to investigate whether a 300-m shuttle run test predicts anaerobic capacity, expressed as mean power output in the Wingate test, in a group of professional soccer players. Twenty-one soccer players (21 ± 2 years; 76.8 ± 7.0 kg; 179.8 ± 6.7 cm) from a first division team of the São Paulo Soccer Federation participated in the study. In the first session, the players were submitted to the Wingate test for the determination of relative peak power output, relative mean power output and fatigue index. In the second session, the players underwent a shuttle run test which consisted of a maximum sprint of 20 m at the highest speed possible until completing a distance of 300 m. The total run time and mean velocity over the 20 m (V20m) were recorded. Blood samples were collected before and after the 300-m shuttle run test for the determination of lactate concentration ([LAC]). Pearson's correlation between the Wingate and 300-m shuttle run test variables showed that only relative mean power output was significantly correlated (p<0.05) with total run time (r = - 0.75) and V20m (r = 0.72). [LAC] showed a significant increase (p<0.05) when comparing the values obtained before (2.1 ± 1.0 mM) and after (14.3 ± 2.4 mM) the shuttle run test. In conclusion, this study demonstrated that the 300-m shuttle run test can predict anaerobic capacity in professional soccer players.
Avaliação da capacidade anaeróbia de jogadores de futebol através de teste máximo de corrida de Vai-e-Vem
Keywords: Blood lactate; Track and field; Wingate test